Property management in the public sector has specific characteristics which differentiates it from the private sector: evidence from an analysis of the South African market - Mukori, Samuel (Department of Construction Economics and Management, 2016)
This thesis investigates the perception of public sector property management professionals on the differences between public and private sector management in South Africa. The main objective of the research is to ascertain if private sector property performance measures are appropriate and sufficient in scope to be used in the public sector. A two-fold quantitative-descriptive survey method was used together with an analysis of the public property management literature. The research established that property management between the two sectors is different mainly due to their different objectives of property ownership, the private sector being profit driven while the public sector is social service delivery oriented. Property composition is also different as the public sector property portfolios are diverse as they include assets that have both financial and non-financial objectives. The study concludes that private sector property performance measures are appropriate for use in the public sector as they address financial issues. However, these measures are insufficient as they tend to ignore non-financial variables that contribute to service delivery which is one of the main reasons for the public sector's existence. Therefore an appropriate and sufficient public sector property performance regime should include both financial and non-financial variables, which can be presented by a service balanced scorecard (SBS) which measures public property's contribution to service delivery.